CHILDREN'S NUTRITIONAL STATUS OF 6-24 MONTHS BASED ON MOTHER KNOWLEDGE ABOUT THE FIRST 1000 DAYS OF LIFE IN SABA VILLAGE - Ni Kadek Mila Utami Dewi; I Gusti Agung Ari Widarti; Pande Putu Sri Sugiani (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2020)
The first thousand days of life are 270 days (nine months) in the womb plus the first 730 days (two years) of a child's life. The first 1000 days of life are very sensitive in optimizing children's growth and determining the quality of their lives in the future. The purpose of this study was to find out the nutritional status of the body based on the level of knowledge of mothers about the first 1000 days of life in Saba Village, Blahbatuh Sub-District, Gianyar. This was an observational study with a cross sectional design with a total sample of 64 people. The sampling technique is the multi stage random sampling method. The type of data collected includes data: sample and respondent identity, body weight, mother's level of knowledge about the first 1000 days of life. Data was collected by interview method and weight assessment. Data analysis uses cross tables and described descriptively. From the results of the study, good nutritional status was 90.6%, over nutritional status was 7.8%, poor nutritional status was 1.6%, and lack of nutritional status was not found. The level of knowledge of mothers in the good category was 70.3%, quite 28.1%, less 1.6%. Mothers have a good level of knowledge of good nutritional status 91.1%, more nutritional status 6.7%, poor nutritional status 2.2%. Mothers who have enough knowledge with good nutritional status 88.9%, nutritional status over 11.1%. Mother of baduta who has less knowledge with good nutritional status 100.0%.Keywords: Nutritional Status, Knowledge Level, First 1000 Days of Life